Formulation development of liposomal coffee extracts and investigation of their antioxidant capacities - Macit, Meltem; Eyüpoğlu, Ozan Emre; Macit, Çağlar; Duman, Gülengül (Elsevier, 2021)
he main objective of this study was to carry out the antioxidant capacity of a liposomal formulation either green coffee extract (GCE) and medium roasted coffee extract (RCE) in aq. and MeOH. First, the coffee beans were milled and medium roasted. The obtained green coffee (GC) and roasted coffee (RC) granules were also extracted into (both aq. and MeOH) (99%) solvents. The solvents were evaporated, and the dry extracts were freeze dried. Then, the soy lecithin (SL) (2% w/v) dispersion was prepared using microfludizer. The obtained SL dispersions were freeze dried by using lyophilizer and then, the GCE and RCE (in aq. and MeOH) dry extracts were incorporated into freeze dried liposomal SL dispersions as a one to fourth portion. The liposomal formulations were titled as SL: GCE and SL: RCE, respectively. The SL: GCE and SL: RCE (either in aq. or MeOH) were characterized and evaluated by dynamic light scattering (DLS) technique. Additionally, the antioxidant capacity of all liposomal formulations was performed using by three different analysis methods; 1,1-diphenyl-2-picrylhydrazyl Radical (DPPH.) Scavenging Activity, Cupric Ion Reducing Antioxidant Capacity (CUPRAC) and Ferric Reducing Antioxidant Power (FRAP), respectively. Moreover, HPLC analysis was performed and phenolic compound such as caffeine, chlorogenic acid, ferulic acid, protocatechuic acid, caffeic acid and rosmarinic acid were evaluated. Finally, the SL: RCE (in MeOH) was formulated as an edible film using solvent casting method. The SL: RCE (in MeOH) extract was incorporated into pullulan (20% w/w) solution. Next, the film was made by using oven at 50 °C and 65% relative humidity (RH). DLS results showed mean diameter of liposomal formulations of SL: RCE and SL: GCE (in MeOH) ranged between 110 and 500 nm. The polydispersity index (PDI) were found around 0.3 and 0.6, respectively. Finally, their average zeta-potential values were obtained ?40 and ?70 mV. It was found that both of the SL: GCE and SL: RCE (in aq. and MeOH) almost twice as much as higher antioxidant capacity then alone GC and RC (in aq. and MeOH) (p < 0.05). According to HPLC results, nanoforms of methanolic coffee extracts (SL: GCE and SL: RCE) had the highest caffeine (2.21%, 2.2%) and chlorogenic acid (1.81%, 0.48%) contents, respectively. These findings have proven to liposomal coffee extract formulation has a strong antioxidant capacity. The final formulation of an edible film of SL: RCE (in MeOH) will be evaluated according to antioxidant capacity as a future work.
Keywords: Antioxidant Activity; Coffee Bean; Extraction; Liposome; Phenolic Compounds